Training on Scout Troop Management and Introduction to Troop Accreditation for Scout Leaders - Mardepi Saputra; Andre Igoresky (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
This service aims to improve the quality of scouting coaching and achieve accreditation for the Scout Troop at the scout leader level through troop management training with an introduction to the concept of troop accreditation. This activity is a response to the need for scout leaders who are able to manage troops effectively and understand the importance of the quality standards set in accreditation. This training provides an in-depth understanding of scout troop management, including activity planning, member management, and character building. In addition, participants are also introduced to the concept of scout troop accreditation, which includes the assessment criteria and performance measurement process for scout troops established by KWARNAS in relation to the implementation of scout troop accreditation. The methods used in this service include interactive material delivery, group discussions, case studies, and simulations. The training participants consisted of Scout leaders from various scout troops. They were actively involved in collaborative learning to improve their understanding and skills in scout troop management and preparation for the implementation of scout troop accreditation. The results of this service are expected to have a positive impact on improving the quality of scout training. With a better understanding of troop management and the importance of accreditation, it is hoped that troops will become more organized, efficient, and oriented towards achieving higher quality standards in the implementation of scouting activities